Flaky-like copper powder and method of producing the same

By employing a flake copper powder with optimized particle characteristics and heat treatment conditions in a non-oxidizing atmosphere, the challenge of achieving high conductivity in solidified films is addressed, resulting in films with resistivity below 20 μΩ·cm.

JP2025039172APending Publication Date: 2025-03-21FUKUDA METAL FOIL & POWDER CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023146063
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-08
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

Existing flake copper powders fail to produce solidified films with resistivity below 1000 μΩ·cm when heated in a non-oxidizing atmosphere without using a reducing agent, limiting their application in components requiring high conductivity.

Method used

A flake copper powder with specific particle size distribution, crystallite size, and BET specific surface area, along with controlled oxygen content and reduction amount, is used to form a solidified film by heat treatment in a nitrogen or argon atmosphere at 200° C. to 250° C.

Benefits of technology

The resulting solidified film exhibits excellent conductivity with a resistivity of less than 20 μΩ·cm, suitable for applications in electrical and thermal conduction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025039172000001
    Figure 2025039172000001
Patent Text Reader

Abstract

To provide a flaky-like copper powder allowed to produce a film excellent in conductivity, in which the film is a solidified film to be produced by heating treatment in a non-oxidizing atmosphere without using a reducer.SOLUTION: Provided is a flaky-like copper powder in which "a 50%-cumulative particle diameter" / "a particle diameter determined from a BET specific surface area of the flaky-like copper powder" is 10 or greater, a frequency of a flaky-like copper particle having a particle diameter of 5.079 μm or smaller is 15% or lower, a frequency of a flaky-like copper particle having a particle diameter of 5.079 μm or greater and 41.081 μm or smaller is 90% or lower, a frequency of a flaky-like copper particle having a particle diameter of 51.19 μm or greater is 5% or lower, a crystallite size on a crystal lattice plane (111) of metal by X-ray diffraction of the flaky-like copper particle is 35 nm or smaller, the BET specific surface area is 1 m2 / g or greater, an oxygen content is 2 wt.% or lower, and a reduction loss is 4 wt.% or lower.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a flaky copper powder. More specifically, the flaky copper powder is capable of producing a solidified film having excellent thermal and electrical conductivity (hereinafter, sometimes referred to as "conductivity"), and the solidified film can be produced by heat treatment in a non-oxidizing atmosphere without using a reducing agent. [Background technology]

[0002] In general, copper is often used to form electrodes and circuits of electronic components, electrically conductive layers such as electromagnetic shielding layers, and thermally conductive layers such as heat dissipation sheets, due to its excellent conductivity and processability as well as its low level of ion migration.

[0003] Copper is easily oxidized in air, and the oxidation progresses further when heated, so it is often heat-treated in a non-oxidizing or reducing atmosphere.

[0004] Copper is used as expanded sheet material or foil for relatively large components, but for small-sized components, the copper is powdered and mixed with a varnish consisting of a polymer resin and an organic solvent to form a paste, which is then applied to the surface of the component or base material using various printing methods to form a coating, which is then solidified by heat treatment to become an electrically conductive film (the film obtained by solidification may be referred to as the "solidified film" hereinafter).

[0005] When the coating is heated within a temperature range in which the polymer resin in the coating solidifies, the volume of the coating shrinks, causing the copper powder particles to come into contact with each other, which is believed to result in the solidified film becoming conductive.

[0006] When a coating film is formed from a paste made by kneading flaky copper powder, which has a wide particle size distribution, a large specific surface area, and a low packing density, with a polymer resin, the contact area between the copper powder particles becomes large, making it easier for conductivity to be exhibited even if the copper powder content in the solidified film is small.

[0007] The present invention aims to provide a flaky copper powder that can produce a solidified film that has low resistivity and high conductivity by heat treating a coating film consisting of flaky copper powder and a polymer resin in a non-oxidizing atmosphere without adding a reducing agent. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] Patent Publication No. 2002-15622 [Patent Document 2] Patent Publication 2005-200734 [Patent Document 3] Patent Publication No. 2017-025393 Summary of the Invention [Problem to be solved by the invention]

[0009] Patent Document 1 describes that when copper powder for through-hole conductive paste is made into disk-shaped copper powder with controlled specific surface area and packing density, it has excellent printability and solder wettability and can produce a coating with a resistivity of 140 μΩ cm or less.

[0010] However, the resistivity of the conductive film described in Patent Document 1 is 10 -4 The resistivity is about Ω·cm, which is higher than the inherent resistivity of copper. -5 The problem is that it cannot be applied to components that require a conductivity of Ω·cm or less.

[0011] Patent Document 2 describes that the copper powder in a conductive paste for external electrodes of a multilayer ceramic capacitor has a uniform particle size distribution and aspect ratio, and describes that when flake-shaped copper powder with an average thickness of 0.2 μm or more is controlled so that the 50% diameter in the particle size distribution is 1 μm to 30 μm, the aspect ratio is 5 to 70, and the ratio of the 90% diameter to the 10% diameter in the particle size distribution is 2 to 5, a conductive paste with excellent paste properties and printability is obtained.

[0012] However, the copper powder described in Patent Document 2 does not include any numerical value for the resistivity of the conductor sintered at 840° C., and the resistivity is -5 There is a risk that it cannot be used for components that require a conductivity of Ω·cm or less.

[0013] Patent Document 3 describes that when the aspect ratio of copper powder is measured for 300 or more particles, the range of aspect ratios from 1.00 to 3.00 is divided into 30 intervals with a width of 0.10, the median of the interval is taken as the representative value of the interval, the number frequency included in the interval is plotted against the median, and a line graph is created by connecting adjacent plots with lines.The slope of all line segments between the median values ​​of 1.35 to 1.85 is either negative or zero.When the copper powder contains multiple types of flat particles with different aspect ratios, spaces are likely to form between the particles, making it easier for gas generated during the formation of the conductor to be released to the outside, and making it less likely for defects such as cracks and blisters to occur in the conductor.

[0014] However, the resistivity of the conductor sintered at 845°C for 20 minutes in a nitrogen atmosphere was 10 -2 The problem is that the resistivity is about Ω·cm, which is higher than the inherent resistivity of copper.

[0015] The inventors of the present invention set solving the above-mentioned problems as a technical task, and as a result of repeated trial production and evaluation, they have found that the ratio of "50% cumulative particle size" / "particle size calculated from the BET specific surface area of ​​the flaky copper powder" is 10 or more, the frequency of flaky copper particles having a particle size of 5.079 μm or less is 15% or less, the frequency of flaky copper particles having a particle size of more than 5.079 μm and 41.081 μm or less is 90% or less, the frequency of flaky copper particles having a particle size of 51.19 μm or more is 5% or less, the crystallite size of the metal crystal lattice plane (111) of the flaky copper particles measured by X-ray diffraction is 35 nm or less, and the BET specific surface area is 1 m 2 / g or more, the oxygen content is 2 wt.% or less, and the reduction loss is 4 wt.% or less, it is possible to produce a solidified film that is suitable for use in parts that require high conductivity, and further, it has been discovered that the solidified film can be produced by heat treatment in a non-oxidizing atmosphere without the addition of a reducing agent, thereby achieving the above technical objective. [Means for solving the problem]

[0016] The above technical problems can be solved by the present invention as follows.

[0017] The present invention relates to a flaky copper powder, the flaky copper powder having a ratio of "50% cumulative particle size" / "particle size calculated from the BET specific surface area of ​​the flaky copper powder" of 10 or more, a frequency of flaky copper particles having a particle size of 5.079 μm or less being 15% or less, a frequency of flaky copper particles having a particle size of more than 5.079 μm and 41.081 μm or less being 90% or less, a frequency of flaky copper particles having a particle size of 51.19 μm or more being 5% or less, a crystallite size of the metal crystal lattice plane (111) of the flaky copper particles by X-ray diffraction being 35 nm or less, and a BET specific surface area of ​​1 m 2 / g or more, the oxygen content is 2% by weight or less, and the reduction loss is 4% by weight or less. It is.

[0018] The present invention also relates to a solidified film obtained by heat treating, in a non-oxidizing atmosphere, a coating film consisting of a solid component in which the weight ratio of the above-mentioned flaky copper powder to polyvinyl butyral is 9:1, and a solvent.

[0019] The present invention also relates to the solidified film, wherein the heat treatment is performed in a temperature range of 200°C or higher and 250°C or lower.

[0020] The present invention also relates to the solidified film, wherein the non-oxidizing atmosphere is a nitrogen atmosphere or an argon atmosphere.

[0021] The present invention also relates to a sintered body having a 50% cumulative particle size of 3 μm or more and 20 μm or less and a BET specific surface area of ​​0.2 m 2 / g or more and 0.5m 2 The method for producing the flaky copper powder includes a step of fluidizing and circulating a slurry consisting of raw copper powder having a molecular weight of 0.1 g / g or less and containing 0.2% by weight or less of unavoidable components other than copper, a mixture of unsaturated fatty acids, and a solvent in a moving medium to perform a spreading treatment, and a step of drying the powder while suppressing oxidation. Effect of the Invention

[0022] The coating film formed from the paste obtained by kneading the flaky copper powder and polymer resin in the present invention becomes a solidified film exhibiting excellent conductivity when heat-treated in a non-oxidizing atmosphere, even without the addition of a reducing agent.

[0023] The polymer resin is polyvinyl butyral, the non-oxidizing atmosphere is a nitrogen atmosphere or an argon atmosphere, and the flake copper powder becomes a solidified film that exhibits even better conductivity when heat-treated at 200°C to 250°C. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] In this specification, the 50% cumulative particle size is sometimes referred to as the "50% diameter," and the particle size calculated from the BET specific surface area of ​​the flaky copper powder is sometimes referred to as the "BET diameter." The spherical volume equivalent particle diameter is referred to as the "particle diameter". Copper powder with a large aspect ratio, which is the ratio of the major axis to the thickness of the powder, is called flake copper powder. The flaky copper powder refers to an aggregate of flaky copper particles.

[0025] In the present invention, the 50% diameter / BET diameter is 10 or more.

[0026] The BET diameter can be calculated from the specific surface area value measured by the BET method using the following formula (1).

[0027] (Formula 1) BET diameter = 6 / (BET specific surface area x true density of copper)

[0028] When the ratio of the 50% diameter measured by the laser diffraction method to the BET diameter calculated from (Equation 1) (50% diameter / BET diameter) was calculated, it was found that this ratio increases as the powder shape changes from spherical to irregular and then to flaky, and this ratio was used as an index value indicating the degree of flake-likeness.

[0029] Copper powder in the form of flakes, spheres, lumps or dendrites, which has an index value of less than 10, is difficult to disperse uniformly in the coating film, which is a mixture with the polymer resin, and is difficult to form a dense film.

[0030] In addition, there is a risk that it will not be possible to produce a solidified film that exhibits excellent conductivity, such as a resistivity of the solidified film being less than 1000 μΩ·cm after heat treatment at 200° C. in a non-oxidizing atmosphere.

[0031] If the 50% diameter / BET diameter exceeds 100, the cumulative amount of input energy during flake processing becomes large, or the processing time becomes long.

[0032] In addition, the BET specific surface area of ​​flake copper powder is 4m 2 / g, which reduces productivity.

[0033] When the specific surface area increases, the amount of oxidation on the powder surface increases, which may make it difficult to produce a solidified film that exhibits excellent conductivity when subjected to heat treatment in a non-oxidizing atmosphere.

[0034] Therefore, the 50% diameter / BET diameter (index value) is preferably 10-100.

[0035] In the flaky copper powder of the present invention, the frequency of flaky copper powder particles having a particle size of 5.079 μm or less (hereinafter sometimes referred to as "frequency 1") is 15% or less.

[0036] Powders with a particle size of 5.079 μm or less easily enter spaces created by contact between the ends of relatively large flake-shaped copper powder particles and cavities created when large flake-shaped copper powder particles come into contact with each other on their surfaces during the process from drying after printing and coating to heat treatment in a non-oxidizing atmosphere. This causes the powder particles to fuse together, increasing the continuity of the flake-shaped copper powder throughout the entire solidified film, thereby reducing resistance and enabling the production of a solidified film that exhibits excellent conductivity when heated in a non-oxidizing atmosphere.

[0037] However, when the frequency 1 exceeds 15%, although the contact resistance can be reduced by entering into the gaps between the ends of powder with a large particle diameter exceeding 5.079 μm, the flaky copper powder with a particle diameter of 5.079 μm or less will adhere more to the flaky copper powder with a particle diameter exceeding 5.079 μm, and the proportion of flaky copper powder with a particle diameter exceeding 5.079 μm that exists between the flat surfaces of each other will increase, which may result in an increase in contact resistance.

[0038] In addition, small flake copper powder particles with a particle diameter of 5.079 μm or less will also aggregate and form lumps, which may reduce the continuity and density of the flake copper powder in the coating film, making it difficult to produce a solidified film that exhibits excellent conductivity when heated in a non-oxidizing atmosphere.

[0039] Furthermore, if the frequency 1 is 4% or less, there is a limit to the effect of reducing the contact resistance between powder particles, and it may become difficult to produce a solidified film that exhibits excellent conductivity by heat treatment in a non-oxidizing atmosphere.

[0040] Therefore, the frequency of flaky copper particles having a particle size of 5.079 μm or less is preferably in the range of 4% to 15%.

[0041] In the flaky copper powder of the present invention, the frequency of flaky copper particles having a particle diameter of more than 5.079 μm and not more than 41.081 μm (hereinafter sometimes referred to as "frequency 2") is 90% or less.

[0042] When frequency 2 exceeds 90%, the frequency of flake copper particles having a particle diameter of 5.079 μm or less decreases, and the proportion of particles having a particle diameter exceeding 5.079 μm decreases. This makes it difficult for the particles to penetrate into the gaps between the ends of the powder having a large particle diameter and reduce the contact resistance, and therefore it may be difficult to produce a solidified film exhibiting excellent conductivity by heat treatment in a non-oxidizing atmosphere.

[0043] When the frequency 2 is 80% or less, the frequency of flake copper particles having a particle diameter of 5.079 μm or less tends to exceed 15%, and the proportion of flake copper powder particles having a particle diameter of more than 5.079 μm that exist between the flat surfaces of each other increases, resulting in increased contact resistance and possibly making it difficult to produce a solidified film exhibiting excellent conductivity by heat treatment in a non-oxidizing atmosphere.

[0044] Therefore, it is preferable that frequency 2 is 80% or more and 90% or less.

[0045] In the flaky copper powder of the present invention, the frequency of flaky copper particles having a particle diameter of 51.19 μm or more (hereinafter sometimes referred to as "frequency 3") is 5% or less.

[0046] If the frequency 3 exceeds 5%, when a paste consisting of flaky copper powder, polymer resin, and a solvent is used to form a coating film by screen printing or the like so that the film thickness after solidification will be 1 μm to 50 μm, the fluidity of the paste may be impaired, resulting in poor removal of the paste from the printing plate, uneven cross-sectional shape of the coating film after printing, and poor surface smoothness, which may result in poor transferability.

[0047] The crystallite size of the copper crystal lattice plane (111) of the flaky copper powder of the present invention, as determined by X-ray diffraction, is preferably 35 nm or less.

[0048] If the diameter exceeds 35 nm, the 50% diameter / BET diameter (index value) will not be 10 or more, and the frequency 1 will not be 15% or less, making it difficult to obtain continuity of the flake copper powder in the coating film that has been heat-treated at 200°C in a non-oxidizing atmosphere.

[0049] The flake copper powder in the present invention has a BET specific surface area of ​​1 m 2 / g or more.

[0050] BET specific surface area is 1m 2 If it is less than 1 / g, the 50% diameter / BET diameter (index value) may not be 10 or more, which may make it difficult to produce a solidified film that exhibits excellent conductivity by heat treatment in a non-oxidizing atmosphere.

[0051] The BET specific surface area of ​​flake copper powder is 4m 2 If it exceeds 1 / g, the amount of energy input and the processing time during flake processing will be long, productivity will be reduced, and the amount of oxidation on the powder surface will be easily increased.

[0052] Therefore, the BET specific surface area is 1m 2 / g~4m 2 It is preferred that the molecular weight is / g.

[0053] The flaky copper powder of the present invention has an oxygen content of 2% by weight or less.

[0054] If the oxygen content exceeds 2% by weight, oxygen-derived copper oxide will remain in the solidified film after heat treatment in a non-oxidizing atmosphere at 200°C, which may make it difficult to produce a solidified film that exhibits excellent conductivity by heat treatment in a non-oxidizing atmosphere.

[0055] The flaky copper powder of the present invention has a reduction loss of 4% by weight or less.

[0056] The reduction weight loss of copper is measured in accordance with JISH2601-1976 by a heating test at 875°C for 30 minutes in a hydrogen stream, and is the component that is present in the copper powder and decomposes at 875°C or lower and is released from the copper powder.

[0057] The main components that are released are copper oxides (oxygen from the oxide layer on the copper surface), and organic matter and moisture adsorbed on the powder surface.

[0058] If the reduction loss exceeds 4% by weight, the solidified film formed from a paste consisting of solids and solvent, with a weight ratio of 9:1 between flake copper powder and polyvinyl butyral (PVB), will contain a large amount of residual copper oxide and other impurities after heat treatment in a non-oxidizing atmosphere at 200°C, making it difficult to produce a solidified film that exhibits excellent conductivity by heat treatment in a non-oxidizing atmosphere.

[0059] In the present invention, a coating film is formed from a paste consisting of solids and a solvent, with the weight ratio of the flaky copper powder and polyvinyl butyral (PVB) being 9:1, and the solidified film produced by heat treatment at 200°C to 250°C in a non-oxidizing atmosphere has a resistivity of less than 1000 μΩ·cm.

[0060] A viscous liquid varnish is produced by mixing and stirring the PVB and solvent while heating them in advance to below 100°C.

[0061] The solvent must be minimally harmful and dangerous, must be easy to dissolve the resin into a varnish, and must not easily cause changes in the viscosity of the paste during long periods of printing.

[0062] Furthermore, when heat treatment is performed in an air atmosphere, the surface oxidation of copper progresses with increasing temperature, so it is preferable that the solvent is almost completely volatilized and separated from the coating film by 150°C.

[0063] Examples of solvents that can be suitably used include butyl carbitol acetate and butyl carbitol.

[0064] The prepared varnish is mixed with flake copper powder and kneaded into a paste using a mixing machine, a three-roll mill, a planetary mixer, or the like.

[0065] In order to optimize the printing suitability, such as the fluidity of the paste, for each printing method, such as screen printing, the solvent used in the varnish may be appropriately added.

[0066] The printing method may be appropriately selected depending on the film thickness, film pattern, etc., and examples thereof include bar coater and screen printing.

[0067] Examples of substrates onto which the prepared paste is applied include heat-resistant resin films such as polyimide, ceramic substrates such as alumina, and electrically insulating substrates such as glass.

[0068] After the coating is formed, it is heat treated at 200℃ to 250℃ in a non-oxidizing and non-reducing atmosphere to produce a solidified film.

[0069] When the solvent in the coating film evaporates and separates, the volume of the coating film shrinks and the flake-like copper powder in the coating film comes into contact with each other and becomes dense.

[0070] If heated in a non-oxidizing and non-reducing atmosphere, the flaky copper powder in the coating is not affected by oxidation, etc., and during heating, small amounts of organic components derived from the flaky copper powder and polymer resin decompose, and the hydrogen and carbon monoxide produced during this process act as electron donors, reducing the copper. It is also believed that the crystals at the ends of the flaky copper powder fuse together through the ends due to atomic diffusion, causing the flaky copper powder in the coating to continuously exhibit conductivity.

[0071] Even if heat treatment is performed in a non-oxidizing, non-reducing atmosphere at less than 200°C, the ends of the flaky copper powder will not fuse together sufficiently, and the continuity of the flaky copper powder parts in the solidified film will be insufficient, making it difficult to achieve a resistivity of less than 1000 μΩ cm and potentially making it difficult to produce a solidified film that exhibits excellent conductivity.

[0072] Examples of non-oxidizing and non-reducing atmospheres include a nitrogen atmosphere and an argon atmosphere.

[0073] The thickness of the solidified film is preferably 1 μm to 50 μm.

[0074] It is practically difficult to form a film having a thickness of less than 1 μm after heat treatment using the flaky copper powder of the present invention.

[0075] Although it is possible to make the film thickness after heat treatment exceed 50 μm, commercially available copper sheets of the same thickness have a resistivity almost equal to that of bulk copper, so there is no practical point in producing a solidified film of this thickness.

[0076] The resistivity of the solidified film is preferably 1000 μΩ·cm or less.

[0077] If the resistivity exceeds 1000 μΩ·cm, heat loss during electrical current flow increases, making it difficult to use for electrical conduction applications such as electrodes.

[0078] In addition, if the resistivity is low, the thermal conductivity is high, and conversely, if the resistivity is high (electrical conductivity is low), the thermal conductivity is low, making it difficult to use in thermal conduction applications such as heat dissipation sheets.

[0079] With the flaky copper powder of the present invention, a paste consisting of a polyvinyl butyral (PVB) solid and solvent in a weight ratio of 9:1 can be heat-treated in a non-oxidizing atmosphere at 200°C to 250°C to produce a solidified film with a low resistivity of less than 20 μΩ·cm, without the need for a reducing agent such as hydrogen or formic acid.

[0080] The 50% diameter of the raw material copper powder is preferably 3 μm to 20 μm.

[0081] If the particle size is less than 3 μm or exceeds 20 μm, the oxygen content tends to exceed 2% by weight.

[0082] Also, the energy input and processing time required for producing the flaky copper powder of the present invention are increased.

[0083] The BET specific surface area of ​​the raw copper powder is 0.2 m 2 / g~0.5m 2 It is preferred that the molecular weight is / g.

[0084] BET specific surface area is 0.2m 2 / g or less than 0.5m 2If it exceeds 1 / g, the oxygen content is likely to exceed 2% by weight.

[0085] Also, the amount of energy input and processing time required to obtain the flaky copper powder of the present invention are increased.

[0086] The amount of unavoidable components other than copper in the raw copper powder is preferably 0.2% by weight or less.

[0087] If the content exceeds 0.2% by weight, unavoidable components will remain at the grain boundaries within the copper crystals of the solidified film after heat treatment at 200°C to 250°C in a non-oxidizing atmosphere, which may make it difficult to produce a solidified film that exhibits excellent conductivity.

[0088] The method for producing flaky copper powder of the present invention preferably includes a step of fluidizing and circulating a slurry consisting of copper powder, a mixture of unsaturated fatty acid, and a solvent within an exercising medium to spread the slurry, and a step of drying the slurry while suppressing oxidation to produce a powder.

[0089] The unsaturated fatty acid is not particularly limited, but oleic acid is preferred.

[0090] The BET specific surface area of ​​copper powder is 1 m 2 / g~4m 2 To achieve this, the amount of unsaturated fatty acid added is preferably 0.5% by weight to 3.0% by weight based on the copper powder.

[0091] If the content is less than 0.5% by weight, it is difficult to produce the flaky copper powder of the present invention, and if it exceeds 3.0% by weight, it will remain as an impurity component in the solidified film after heat treatment at 200°C in a non-oxidizing atmosphere, which may make it difficult to produce a solidified film that exhibits excellent conductivity by heat treatment in a non-oxidizing atmosphere.

[0092] Also, there is a risk that the robustness of the solidified film and the adhesive strength between the solidified film and the substrate may be impaired.

[0093] Although the solvent for making the raw copper powder into a slurry is not particularly limited, methyl alcohol is preferred because it allows drying treatment at a low temperature of 60° C. or less, which is capable of suppressing the progress of oxidation of copper.

[0094] Water can also be used as the solvent, but when water is used, it is preferable to add a hydrophilic lubricant or surfactant.

[0095] In addition, since oxidation of copper easily proceeds during the drying treatment, it is preferable to appropriately add a known hydrophilic antioxidant.

[0096] An example of a hydrophilic antioxidant is benzotriazole.

[0097] The concentration of copper powder in the slurry is preferably 20% by weight to 40% by weight.

[0098] If the content is less than 20% by weight or exceeds 40% by weight, the probability of contact between the media and the copper powder decreases, resulting in a longer treatment time.

[0099] Examples of equipment used in the process of spreading a slurry of copper powder, a solvent, and an unsaturated fatty acid by fluidizing and circulating it in a moving medium include a ball mill and a media stirring mill.

[0100] The media filled in the device may be made of bearing steel or zirconia, with zirconia being preferred as it is less abraded during processing.

[0101] When forming flaky copper powder, the media diameter is preferably 10 to 150 times the 50% diameter of the raw copper powder.

[0102] The amount of media to be filled is preferably 60 vol % to 70 vol % of the volume of the processing chamber of the apparatus.

[0103] The centrifugal force, which is the kinetic energy of the media being processed, can be expressed as the rotation speed.

[0104] The optimum values ​​for the characteristics of the raw copper powder, the slurry concentration, the media material and the media diameter should be selected. EXAMPLES

[0105] The present invention will be described with reference to examples and comparative examples, but the present invention is not limited to these.

[0106] The 50% diameter of the copper powder was measured using a laser diffraction particle size distribution measuring device SALD-2300 (manufactured by Shimadzu Corporation).

[0107] The BET specific surface area of ​​the copper powder was measured using a fully automatic BET specific surface area measuring device, Macsorb HM-1208 (manufactured by Mountec Co., Ltd.).

[0108] The amount of unavoidable components in the raw copper powder was defined as the total amount of oxygen, nitrogen, carbon, sulfur, and other elemental components.

[0109] The amount of oxygen was measured by placing copper powder in a graphite crucible and melting it in a He atmosphere using an oxygen / nitrogen analyzer ON830 (manufactured by LECO Japan LLC). The oxygen in the powder was reduced by the carbon in the graphite crucible and extracted as carbon monoxide, which was then converted to gas weight using an infrared detector.

[0110] The amount of nitrogen was determined by absorbing and separating the carbon dioxide and moisture produced by heating and melting, and converting the remaining nitrogen into gas weight using a thermal conductivity detector.

[0111] The weight of the converted gas was divided by the weight of the sample that had been weighed in advance to calculate the amount of carbon and the amount of sulfur.

[0112] Using an EMIA-920V carbon / sulfur analyzer (manufactured by Horiba, Ltd.), flake copper powder was burned together with a combustion improver in an oxygen carrier, converting the carbon into carbon dioxide and carbon monoxide, and the sulfur into sulfur dioxide. These were then introduced into a non-dispersive infrared gas analyzer, where a signal change corresponding to the gas concentration occurred due to the infrared absorption characteristics of the gas. This signal change was processed to calculate the gas weight.

[0113] The calculated values ​​were divided by the weight of the sample, which had been weighed in advance, to calculate the amounts of oxygen and nitrogen.

[0114] Other elemental components were measured using a fluorescent X-ray analyzer ZSX PrimusV (Rigaku Corporation).

[0115] The BET diameter was calculated from the specific surface area of ​​the flaky copper powder measured by the BET method using the following formula (1).

[0116] (Formula 1) BET diameter = 6 / (BET specific surface area x true density of copper)

[0117] The true density of copper is 8.94g / cm 3 The calculation was done as follows.

[0118] The ratio of the 50% diameter measured by the laser diffraction method to the BET diameter calculated from (Equation 1) (50% diameter / BET diameter) was calculated and used as an index value of the degree of flake shape.

[0119] The frequency of particle diameters of 5.079 μm or less (frequency 1), the frequency of particle diameters of more than 5.079 μm and 41.081 μm or less (frequency 2), and the frequency of particle diameters of 51.19 μm or more (frequency 3) were measured using a laser diffraction particle size distribution analyzer SALD-2300 (manufactured by Shimadzu Corporation).

[0120] The copper crystallite size of the flake copper powder was measured using an Ultima IV (Rigaku Corporation) with a copper target Kα ray in the measurement range 2θ = 20° to 100°, and calculated from the integral width of the X-ray diffraction peak in the copper crystal lattice plane (111) using the following Scherrer formula (Equation 2).

[0121] (Formula 2) Scherrer's formula: D=Kλ / βcosθ D: Crystallite size in the direction perpendicular to the (111) crystal lattice plane λ: wavelength of the target X-ray (Cukα) β: Broadening of diffraction lines due to crystallite size [rad] θ: Diffraction angle K: Scherrer constant (half-width β 1 / 2 If we use 0.9)

[0122] The reduction weight loss of the flaky copper powder was measured in accordance with JISH2601-1976 by a heating test at 875°C for 30 minutes in a hydrogen stream.

[0123] The oxygen content of the flaky copper powder was measured using an oxygen / nitrogen analyzer ON830 (manufactured by LECO Japan LLC).

[0124] The resistivity of the solidified film (=R×t×b / L) was calculated as follows.

[0125] The film width (b) of the solidified film was measured using a surface profiler DEKTAK3 (manufactured by ULVAC, Inc.).

[0126] The length (L) of the solidified film was measured using a C-type JIS Class 1 ruler (manufactured by Shinwa).

[0127] The resistance value (R) of the solidified film was measured by the four-terminal method using a Milliohm Hitester 3540 (manufactured by Hioki E.E. Corporation).

[0128] The thickness (t) of the solidified film was measured using a surface profiler DEKTAK3 (manufactured by ULVAC, Inc.).

[0129] Example 1 The raw material has a 50% diameter of 16.897 μm and a BET specific surface area of ​​0.43 m 2 / g, and 0.19 wt % of unavoidable components other than copper was used.

[0130] 2.0% by weight of oleic acid (manufactured by Kanto Chemical Co., Ltd.) was added to the raw material powder. Methyl alcohol (manufactured by Kanto Chemical Co., Ltd.) was used as a solvent to adjust the slurry concentration to 20% by weight.

[0131] In an SC mill, model SC50 (manufactured by Nippon Coke and Engineering Co., Ltd.), zirconia media with a diameter of 0.5 mm were filled in the treatment chamber to a concentration of 67 vol %.

[0132] After treatment at 3000 rpm for 2 hours, drying treatment was carried out in an air atmosphere at 60° C. for 4 hours using a hot air dryer WFO-420W (manufactured by Tokyo Rikakikai Co., Ltd.) to obtain a flake-shaped copper powder.

[0133] The resulting flake copper powder has a BET specific surface area of ​​2.55 m 2 / g and the 50% diameter was 18.15 μm.

[0134] The 50% diameter / BET diameter (index value) was 68.97, frequency 1 was 4.99%, frequency 2 was 87.15%, frequency 3 was 3.21%, the crystallite size of the metal crystal lattice plane (111) determined by X-ray diffraction was 33.3 nm, the oxygen content was 1.50 wt%, and the reduction loss was 2.87 wt%.

[0135] Polyvinyl butyral (PVB) resin BL-S (manufactured by Sekisui Chemical Co., Ltd.) was dissolved in butyl carbitol acetate (manufactured by Kanto Chemical Co., Ltd.) to a concentration of 30% by weight to prepare a varnish.

[0136] The varnish was mixed with the flaky copper powder in a planetary mixer ARE-310 (Thinky Corporation) to produce a paste, so that the solid content was 90% by weight.

[0137] The prepared paste was applied to MICRO SLIDE GLASS S-7213 (manufactured by Matsunami Glass Industry Co., Ltd.) by attaching a tape approximately 50 μm thick to a width of 5 mm, and then squeegeeing with a flat thin plate to form a coating film to ensure a uniform thickness.

[0138] The mixture was heated to 200° C. in an atmospheric tube furnace KTF045N-AS (manufactured by Koyo Thermo Systems Co., Ltd.) while maintaining a nitrogen gas atmosphere, and held for 30 minutes to obtain a solidified film.

[0139] The resistivity of the solidified film obtained was 612 μΩ·cm.

[0140] Example 2 A solidified film was obtained in the same manner as in Example 1, except that the substrate was heated to 250° C. while maintaining the nitrogen gas atmosphere and held for 30 minutes.

[0141] The resistivity of the solidified film obtained was 14.2 μΩ·cm.

[0142] Example 3 The raw material has a 50% diameter of 4.049 μm and a BET specific surface area of ​​0.27 m 2 / g, and 0.11 wt % of unavoidable components other than copper was used.

[0143] Oleic acid (manufactured by Kanto Chemical Co., Ltd.) was added to the copper powder so that the concentration became 2.0% by weight, and methyl alcohol (manufactured by Kanto Chemical Co., Ltd.) was added so that the slurry concentration became 20% by weight.

[0144] Using an SC mill, model SC50 (manufactured by Nippon Coke and Engineering Co., Ltd.), zirconia media with a diameter of 0.5 mm were packed in the treatment chamber to a concentration of 67 vol %.

[0145] After processing at 3000 rpm for 2 hours, the mixture was dried in an air atmosphere at 60° C. for 4 hours using a hot air dryer WFO-420W (manufactured by Tokyo Rikakikai Co., Ltd.) to produce a flaky copper powder.

[0146] The flake copper powder produced has a BET specific surface area of ​​2.44 m 2 / g, and the 50% diameter was 14.142 μm.

[0147] The 50% diameter / BET diameter (index value) was 51.41, frequency 1 was 13.79%, frequency 2 was 85.08%, frequency 3 was 0.00%, the crystallite size of the metal crystal lattice plane (111) determined by X-ray diffraction was 34.2 nm, the oxygen content was 2.00 wt%, and the reduction loss was 3.92 wt%.

[0148] A solidified film was obtained in the same manner as in Example 1. The resistivity of the solidified film was 800 μΩ·cm.

[0149] Example 4 A solidified film was obtained in the same manner as in Example 3, except that the substrate was heated to 250°C while maintaining the nitrogen gas atmosphere and held for 30 minutes. The resistivity of the solidified film was 16.1 μΩ cm.

[0150] Comparative Example 1 The raw material has a 50% diameter of 16.897 μm and a BET specific surface area of ​​0.43 m 2 / g, and 0.19 wt % of unavoidable components other than copper was used.

[0151] Oleic acid (manufactured by Kanto Chemical Co., Ltd.) was added to the copper powder so that the concentration became 2.0% by weight, and then methyl alcohol (manufactured by Kanto Chemical Co., Ltd.) was added so that the slurry concentration became 20% by weight.

[0152] In an SC mill, model SC50 (manufactured by Nippon Coke and Engineering Co., Ltd.), zirconia media with a diameter of 0.5 mm were packed in the treatment chamber to a concentration of 67 vol%.

[0153] After processing at 3000 rpm for 0.5 hours, the mixture was dried in an air atmosphere at 60° C. for 4 hours using a hot air dryer WFO-420W (manufactured by Tokyo Rikakikai Co., Ltd.) to produce a flaky copper powder.

[0154] The BET specific surface area of ​​the produced flake copper powder is 0.76 m 2 / g and the 50% diameter was 10.602 μm.

[0155] The 50% diameter / BET diameter (index value) was 12.01, frequency 1 was 16.18%, frequency 2 was 83.46%, frequency 3 was 0.04%, the crystallite size of the metal crystal lattice plane (111) determined by X-ray diffraction was 37.3 nm, the oxygen content was 0.70 wt%, and the reduction loss was 2.35 wt%.

[0156] A solidified film was obtained in the same manner as in Example 1. The resistivity of the solidified film was 1720 μΩ·cm.

[0157] Comparative Example 2 Except for heating to 250°C while maintaining the nitrogen gas atmosphere and holding the treatment for 30 minutes, a solidified film was obtained in the same manner as in Comparative Example 1. The resistivity of the solidified film was 58.7 μΩ·cm.

[0158] Comparative Example 3 The raw material has a 50% diameter of 16.897 μm and a BET specific surface area of ​​0.43 m 2 / g, and 0.19 wt % of unavoidable components other than copper was used.

[0159] Oleic acid (manufactured by Kanto Chemical Co., Ltd.) was added to the copper powder so that the concentration became 2.0% by weight, and then methyl alcohol (manufactured by Kanto Chemical Co., Ltd.) was added so that the slurry concentration became 20% by weight.

[0160] Using an SC mill, model SC50 (manufactured by Nippon Coke and Engineering Co., Ltd.), zirconia media with a diameter of 0.5 mm were packed in the treatment chamber to a concentration of 67 vol %.

[0161] After processing at 3000 rpm for 4 hours, the mixture was dried in an air atmosphere at 60° C. for 4 hours using a hot air dryer WFO-420W (manufactured by Tokyo Rikakikai Co., Ltd.) to produce a flaky copper powder.

[0162] The BET specific surface area of ​​the produced flake copper powder is 4.52 m 2 / g, and the 50% diameter was 15.051 μm.

[0163] The 50% diameter / BET diameter (index value) was 101.37, frequency 1 was 11.09%, frequency 2 was 82.38%, frequency 3 was 2.49%, the crystallite size of the metal crystal lattice plane (111) determined by X-ray diffraction was 31.1 nm, the oxygen content was 2.50 wt%, and the reduction loss was 4.47 wt%.

[0164] A solidified film was obtained in the same manner as in Example 1. The resistance value of the solidified film was immeasurable, indicating that it was insulating.

[0165] Comparative Example 4 A solidified film was obtained in the same manner as in Comparative Example 3, except that the substrate was heated to 250°C while maintaining the nitrogen gas atmosphere and held for 30 minutes. The resistivity of the solidified film was 36.4 μΩ·cm.

[0166] Comparative Example 5 The raw material has a 50% diameter of 1.84 μm and a BET specific surface area of ​​0.57 m 2 / g, and 0.13 wt % of unavoidable components other than copper was used.

[0167] Oleic acid (manufactured by Kanto Chemical Co., Ltd.) was added to the copper powder so that the concentration became 2.0% by weight, and then methyl alcohol (manufactured by Kanto Chemical Co., Ltd.) was added so that the slurry concentration became 20% by weight.

[0168] Using an SC mill, model SC50 (manufactured by Nippon Coke and Engineering Co., Ltd.), zirconia media with a diameter of 0.3 mm were filled in the treatment chamber to a concentration of 67 vol %.

[0169] After processing at 3000 rpm for 2 hours, the mixture was dried for 0.5 hours in an air atmosphere at 60° C. using a hot air dryer WFO-420W (manufactured by Tokyo Rikakikai Co., Ltd.) to produce flaky copper powder.

[0170] The BET specific surface area of ​​the produced flake copper powder was 0.84 m 2 / g, and the 50% diameter was 3.48 μm.

[0171] The 50% diameter / BET diameter (index value) was 4.36, frequency 1 was 79.06%, frequency 2 was 20.95%, frequency 3 was 0.00%, the crystallite size of the metal crystal lattice plane (111) determined by X-ray diffraction was 32.99 nm, the oxygen content was 1.00 wt%, and the reduction loss was 3.22 wt%.

[0172] A solidified film was obtained in the same manner as in Example 1. The resistivity of the solidified film was 34,100 μΩ·cm.

[0173] Comparative Example 6 A solidified film was obtained in the same manner as in Comparative Example 5, except that the substrate was heated to 250°C while maintaining the nitrogen gas atmosphere and held for 30 minutes. The resistivity of the obtained solidified film was 108 μΩ cm.

[0174] Comparative Example 7 The raw material has a 50% diameter of 4.414 μm and a BET specific surface area of ​​0.21 m 2 / g, and 0.12 wt % of unavoidable components other than copper was used.

[0175] Oleic acid (manufactured by Kanto Chemical Co., Ltd.) was added to give a concentration of 2.0% by weight, and then methyl alcohol (manufactured by Kanto Chemical Co., Ltd.) was added to give a slurry concentration of 20% by weight.

[0176] Using an SC mill, model SC50 (manufactured by Nippon Coke and Engineering Co., Ltd.), zirconia media with a diameter of 0.5 mm were packed in the treatment chamber to a concentration of 67 vol %.

[0177] After processing at 3000 rpm for 0.5 hours, the mixture was dried in an air atmosphere at 60° C. for 4 hours using a hot air dryer WFO-420W (manufactured by Tokyo Rikakikai Co., Ltd.) to produce a flake-shaped copper powder.

[0178] The BET specific surface area of ​​the produced flake copper powder was 0.50 m 2 / g, and the 50% diameter was 11.266 μm.

[0179] The 50% diameter / BET diameter (index value) was 8.39, frequency 1 was 7.33%, frequency 2 was 92.667%, frequency 3 was 0.00%, the crystallite size of the metal crystal lattice plane (111) determined by X-ray diffraction was 38.00 nm, the oxygen content was 0.50 wt%, and the reduction loss was 1.79 wt%.

[0180] A solidified film was obtained in the same manner as in Example 1. The resistivity of the obtained solidified film was 18,200 μΩ·cm.

[0181] Comparative Example 8 A solidified film was obtained in the same manner as in Comparative Example 7, except that the substrate was heated to 250°C while maintaining the nitrogen gas atmosphere and held for 30 minutes. The resistivity of the obtained solidified film was 55.2 μΩ cm.

[0182] Comparative Example 9 The raw material has a 50% diameter of 4.049 μm and a BET specific surface area of ​​0.27 m 2 / g, and 0.11 wt % of unavoidable components other than copper was used.

[0183] Oleic acid (manufactured by Kanto Chemical Co., Ltd.) was added to give a concentration of 2.0% by weight, and then methyl alcohol (manufactured by Kanto Chemical Co., Ltd.) was added to give a slurry concentration of 20% by weight.

[0184] Using an SC mill, model SC50 (manufactured by Nippon Coke and Engineering Co., Ltd.), zirconia media with a diameter of 0.5 mm were filled into the treatment chamber to a concentration of 67 vol%. After treatment at 3000 rpm for 4 hours, a hot air dryer WFO-420W (manufactured by Tokyo Rikakikai Co., Ltd.) was used to dry the mixture in an air atmosphere at 60°C for 4 hours to produce flake copper powder.

[0185] The BET specific surface area of ​​the prepared flake copper powder was 5.45 m 2 / g and the 50% diameter was 15.586 μm.

[0186] The 50% diameter / BET diameter (index value) was 126.57, frequency 1 was 13.93%, frequency 2 was 82.69%, frequency 3 was 0.50%, the crystallite size of the metal crystal lattice plane (111) determined by X-ray diffraction was 32.6 nm, the oxygen content was 3.50 wt%, and the reduction loss was 6.08 wt%.

[0187] A solidified film was obtained in the same manner as in Example 1. The resistance value of the obtained solidified film was immeasurable, indicating that it was insulating.

[0188] Comparative Example 10 A solidified film was obtained in the same manner as in Comparative Example 9, except that the substrate was heated to 250°C while maintaining the nitrogen gas atmosphere and held for 30 minutes. The resistivity of the obtained solidified film was 217 μΩ cm.

[0189] The results are shown in Table 1. The crystallite size of the (111) crystal lattice plane of a metal determined by X-ray diffraction is referred to as the "crystallite." "Temperature" indicates the temperature at which the sample was treated in a nitrogen atmosphere for 30 minutes. "∞" indicates an insulating region.

[0190] [Table 1] [Industrial Applicability]

[0191] The flaky copper powder of the present invention is a flaky copper powder capable of producing a solidified film having excellent conductivity. The solidified film can be produced by heat treatment in a non-oxidizing atmosphere without using a reducing agent, and is a solidified film that can be suitably used in the field of electrical conductivity such as electrodes and circuits, and in the field of thermal conductivity such as heat dissipation sheets. Therefore, the present invention has high industrial applicability.

Claims

1. A flaky copper powder, comprising: The "50% cumulative particle size" / "particle size calculated from the BET specific surface area of ​​the flaky copper powder" is 10 or more, the frequency of flaky copper particles having a particle size of 5.079 μm or less is 15% or less, the frequency of flaky copper particles having a particle size of more than 5.079 μm and 41.081 μm or less is 90% or less, the frequency of flaky copper particles having a particle size of 51.19 μm or more is 5% or less, the crystallite size of the metal crystal lattice plane (111) by X-ray diffraction of the flaky copper particles is 35 nm or less, and the BET specific surface area is 1 m 2 / g or more, the oxygen content is 2% by weight or less, and the reduction loss is 4% by weight or less.

2. 2. A solidified film obtained by heat treating a coating film comprising a solid component and a solvent, the solid component being the flaky copper powder according to claim 1 and polyvinyl butyral in a weight ratio of 9:1, in a non-oxidizing atmosphere.

3. 3. The solidified film according to claim 2, wherein the heat treatment is performed at a temperature in the range of 200°C or higher and 250°C or lower.

4. 3. The solidified film according to claim 2, wherein the non-oxidizing atmosphere is a nitrogen atmosphere or an argon atmosphere.

5. The 50% cumulative particle size is 3 μm or more and 20 μm or less, and the BET specific surface area is 0.2 m 2 / g or more and 0.5m 2 2. A method for producing flaky copper powder according to claim 1, comprising the steps of: fluidizing and circulating a slurry of raw copper powder, the raw copper powder having a molecular weight of 0.1g or less and containing 0.2% by weight or less of unavoidable components other than copper, a mixture of unsaturated fatty acids, and a solvent, in a moving medium to perform a spreading treatment; and drying the powder while suppressing oxidation.

Citation Information

Patent Citations

  • Copper powder for electro-conductive paste and its manufacturing method

    JP2002015622A

  • Flaky copper powder, and its production method

    JP2005200734A

  • Copper powder and manufacturing method thereof

    JP2017025393A